International Health Regulations (2005): public health event communications in the Western Pacific Region - Fearnley, Emily; Li, Ailan (Western Pacific Surveillance and Response, 2013)
This is a brief report covering communications on public health events of international concern in the Western Pacific Region 2007- 2012